Crystal structure of bis(acetylacetonato)bis(quinoline)nickel(II), Ni(C5H14O2N)(2)(C9H7N)(2) - Zukerman-Schpector, J.; Caracelli, I.; Trindade, A. C.; Cussigh, O.; Dunstan, P. O. (Oldenbourg Verlag, 2006)
C28H28N2NiO4, triclinic, P (1) over bar (no. 2), a = 7.9202(6) angstrom, b = 8.0496(6) angstrom, c = 10.246(1) angstrom, alpha = 97.15(1)degrees, beta = 106.68(1)degrees, gamma = 94.686(9)degrees, V = 616.1 angstrom(3), Z = 1, R-gt(F) = 0.028, wR(ref)(F-2) = 0.078, T = 293 K.